Students' perceptions of the academic performance of student-athletes in a state university - Cruz, Rein Danielle M. 2000-; Kho, Edward (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
The study aims to determine perceptions about student-athletes ability to balance their academics with their sport, investigate the actual perceptions, and examine the context behind these perceptions through their non-athlete students' counterparts in a state university through an exploratory sequential mixed-method approach. In Method 1, survey questionnaires were conducted to 50 non-athlete students and analyzed through mean scores and standard deviation. In Method 2, an in-depth interview and open-ended questions were conducted on 6 undergraduate students and analyzed through a thematic analysis. The results have shown that on average, non-athlete students have somewhat to moderately agreed that there is a role interference between sports and academics. In Method 2, non-athlete students expressed that student-athletes have social, academic, and institutional support at the university. Further, non-athlete students dominantly perceived student-athletes in a negative light where they are known to prioritize their sports over education resulting in their academic incompetence. The context of these perceptions is through social media and the personal and shared experiences of their co-students. Findings from the present study suggest raising awareness and stimulating discussion on existing perceptions toward student-athletes so the members of the academe will be able to evaluate how they contribute to the perpetuation of these notions.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Keywords: College athletes; Academic achievement